Pengembangan Media Pembelajaran Berbasis Belajar Sambil Bermain Development Of Learning Media Based On Learning While Playing - Pardede, Lukman; Sihotang, Widia; Simbolon, Florenta; Togatorop, Yesi; Simanjuntak, Yulia; Harianja, Sri; Simanjuntak, Renol (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
Learning is a process of developing knowledge, skills, and attitudes that is carried out by interacting intensively with learning resources. Learning while playing is fun learning because it is a learning process that takes place in a happy and impressive atmosphere that can attract children's interest to be actively involved, so that learning objectives can be achieved optimally. Learning activities while playing are activities that are carried out with feelings of pleasure, without coercion, but have methods that are expected to be able to create results for good development for the child. The method used is learning while playing, because the existence of a world of play within the scope of children's learning can make learning for children more effective, because the world of children is a world of play, it must be balanced with learning, so the learning while playing method is an effective method in learning for children. In this activity we apply three learning methods, namely the Pesonal Room, this program is an activity that gives freedom for students to study with their own learning methods. Mathematical thinking space, aims for students to have the ability to understand mathematical concepts as a whole, develop mathematical reasoning skills and problem solving skills. Dreamtime Room, the application of learning using this method will train students' means of communication to increase self-confidence and self-quality of students.